Causes and effects of visual pollution in the architecture and the image of Arequipa city - Yemy Asunción Alemán Achata (2019)
This study was conducted at the Ejercito, and Andres Avelino Caceres Avenues, which have an intense commercial activity, and one of the largest sources of visual pollution. Based in case research, the focus was in the problematic derivate from visual pollution with a qualitative and quantitative approach, firstly by obtaining information from various sources, through observation to identify places, secondly to conduct to know the opinion about elements, causes, effects, visual pollution. Finally, the analysis and processing of data where the main pollutants and visual information that shows the problem of visual pollution identified in the areas of greatest impact are revealed. Through this research, the intention is to identify the main pollutants that present these avenues, the visual impact on users that pass every day and the magnitude of the influence of such pollution in the urban landscape and in the image of the city too. This work is an important contribution to raising awareness of both government agencies as the public in general, so they can develop common strategies of intervention to solve this problem, which should be based primarily on an adequate regulatory framework to prevent abuses that affect the population and the image of the city.